Tinjauan Filsafat Seni terhadap Tata Rias dan Busana Pengantin Paes Ageng Kanigaran Gaya Yogyakarta - Widayanti, Sri (Jurnal Filsafat "WISDOM", 2011)
The bridal make up and fashion of Yogyakarta’s style, namely Paes Ageng Kanigaran, is a sacred Paesan style in Javanese tradition that has come down through generations as a national heritage. Since the Yogyakarta’s Paes Ageng Kanigaran, with Ngayogyakarta Palace as its source, has standard rules or provisions, its principle meanings will not change. Various elements are used to construct or assemble bridal make-up and fashion of the Yogyakarta’s Paes Ageng Kanigaran; each of them as well as the whole of them has profound philosophical meanings.The interview is used in the field research for this study as a method of collecting data. The data are analysed using several methods, those are: descriptive, Verstehen, interpretative, hermeneutical, comparative, and heuristically methods.The results show that the contents/meanings of the Paes Ageng Kanigaran style are found in the elements used to organize the bridal make-up and fashion of Paes Ageng Kanigaran, while its external form constitutes the whole. The style always experiences growth for it contains aesthetic values as elements of the art of paes which can make someone looks differently beautiful (manglingi).Keywords: wedding dress, fashion, Paes Ageng Kanigaran, aesthetic